Evaluation of the impact of thyroiditis development in patients receiving immunotherapy with programmed cell death-1 inhibitors. (September 2019) - Lei, Matthew; Michael, Angela; Patel, Seema; Wang, Ding
Purpose: We evaluated if the development of thyroiditis in patients who received treatment with immune checkpoint inhibitors across various tumor types was associated with tumor response. Methods: In this retrospective, single-center, cross-sectional study, patients with various tumor types who received treatment with nivolumab or pembrolizumab as standard of care were evaluated. The primary endpoint was to evaluate the objective response rate in patients who developed thyroiditis compared with patients who did not develop thyroiditis. Secondary endpoints included disease control rate, progression-free survival, and overall survival. Results: One hundred and three patients were included for analysis with a median follow-up duration of 12.8 months (range, 4.0–21.6). The data cutoff was 31 December 2016. The objective response rate was 38.2% among the 34 patients in the thyroiditis group and 17.4% in the 69 patients in the non-thyroiditis group (p = 0.028). Progression-free survival was longer in the thyroiditis group than in the non-thyroiditis group. The median progression-free survival was 10.1 months (95% CI, 1.6–18.5) in the thyroiditis group and 3.7 months (95% CI, 2.5–4.9) in the non-thyroiditis group (hazard ratio, 0.45; 95% CI, 0.27–0.76; p = 0.002). Conclusion: Patients with various tumor types who received treatment with immune checkpoint inhibitors and developed thyroiditis had a higher objective response rate than those who did not develop thyroiditis. The development of thyroiditis should be investigated further in the context of prospective randomized trials as a surrogate marker for tumor response to treatment with immune checkpoint inhibitor therapies.